Not a great winner, but an ordinary loser = No un triunfador, sino un simple perdedor - Villanea Morales, Marta Lucía 1962-
This essay presents a characterization analysis of F. Scott Fitzgerald's The Great Gatsby. Being aware of his underprivileged origin, Jay Gatsby spends his whole life amassing his fortune. By examining his behavior in the novel, it is feasible to acknowledge his level of ambition, corruption, alienation, and ultimately loss. In spite of Gatsby's apparent greatness, failure and decay govern his whole life. He was born not only with delusions of greatness but also with the ability of being corrupt; in his attempt of belonging to the aristocratic class, he loses both everything he has longed for and his own life. Thus, Gatsby's unreachable dream makes him an ordinary loser, who is only skilled at making money from dirty business.